Chemical Modification of Banana Peels and Banana Pseudostem for the Adsorptive Removal of Chromium (VI) from Aqueous Solution - Adhikari, Sujata; Subedi, Krishna; Dhungana, Sabin; Arhyal, Ram Lochan; Paudyal, Hari; Ghimire, Kedar Nath; Poudel, Bhoj Raj; Pokhrel, Megh Raj (Journal of Nepal Chemical Society, 2023)
The removal of Cr(VI) from the water was studied using raw and modified banana peels and pseudostem wastes as bio-adsorbent under the batch adsorption technique at room temperature. The chemical modification of raw adsorbents was performed by treating them with concentrated sulphuric acid. Characterizations were performed by FTIR, XRD, and SEM analyses. The raw form of adsorbents showed insignificant adsorption compared to the charred form. Therefore, the further process was carried out using modified adsorbents only. The maximum adsorption capacity for charred banana peel (CBP) and charred banana pseudostem (CBS)was found to be maximum at optimum equilibrium pH 2. The adsorption data fitted well with the Langmuir adsorption model and followed pseudo-second-order kinetics. Therefore, owing to high efficiency and low cost with maximum removal percentage, thus prepared adsorbents are expected to be used satisfactorily in the adsorption of Cr(VI) from aqueous solutions.